Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan, dan Penerapan E-Filing terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi - Juardi Juardi; Mjutiara Husnul Hatimah (AKRUAL : Jurnal Akuntansi dan Keuangan, 2021)
This study aims to find out the factors that affect the level of taxpayer compliance for private taxpayers. The population of this study includes Private Taxpayers who are in KPP Pratama Pondok Gede. The independent variables of this study are Taxpayer Awareness, Quality of Service and Application of E-Filing. The dependent variable of the study is the Personal Taxpayer Compliance Rate. This research method uses Structural Equation Modelling (SEM) with partial least square (PLS) approach and uses SmartPLS 3.0 software to analyze data. The results of this study showed that Taxpayer Awareness had no significant effect on the Level of Compliance of Personal Taxpayers, Quality of Service had a positive and significant effect on the Level of Compliance of Private Taxpayers and the Application of E-Filing had a positive and significant effect on Personal Taxpayer Compliance.